2011
DOI: 10.1007/s10875-011-9634-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Hyperglycemia on IL-10 and TNF-α Production: The Relationship with Perinatal Outcomes

Abstract: Compared to GM <100 mg/dL, GM ≥100 mg/dL was associated with a reduction in maternal IL-10 and TNF-α concentrations and increased placental TNF-α production. Placental IL-10 production was similar in both groups studied and directly correlated with hemoglobin and umbilical cord insulin levels, as well as with the 1- and 5-min Apgar scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
2
18
2
2
Order By: Relevance
“…After screening titles and abstracts, 31 references were selected for full-text reading [16][17][18][19][20][21][22][23][24][25][26][27][28][29][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and 23 citations reporting on 22 studies were included in this review (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts, 31 references were selected for full-text reading [16][17][18][19][20][21][22][23][24][25][26][27][28][29][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and 23 citations reporting on 22 studies were included in this review (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its anti-inflammatory properties, IL-10 has also been investigated in GDM and other hyperglycemic conditions 9,53,60 . Four studies included in this review reported lower concentration of IL-10 in patients with GDM compared with healthy pregnant women, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased synthesis, plasma cytokine levels may not be influenced due to the presence of various factors that prevent the transition of cytokines into the circulation. Among these factors, hypoxic environment due to hyperglycemia and pre-existing inflammatory conditions should be encountered [47]. According to our study, TNF-α appears to be associated more closely than other cytokines with poor glycemic control and oxidative stress parameters.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the increase in placental TNF-α, its plasma levels may not alter due to the presence of various factors which is known to affect the transition of placental secretion through the circulation. Among these factors, hypoxia resulted from hyperglycemic environment and pre-existing inflammatory condition should be taken into account [34,35]. Previous studies with regard to IL-10 levels in GDM are not concordant [15,19,25,26,36].…”
Section: Discussionmentioning
confidence: 96%